Análisis del formato multimedia de las noticias deportivas de las plataformas web del canal de televisión, Ecuavisa y la radio Súper k 800, frente a la construcción de nuevas tendencias interactivas - Caamaño Iturralde, Juan Sebastián (2020)
This research was based on a study on the "Analysis of the multimedia format of the sports news of the web platforms of the television channel, Ecuavisa and the Super k 800 radio, facing the construction of new interactive trends", where it is considered to identify the flaws of traditional media when uploading news on their digital portals. Therefore, this research is about finding the shortcomings of the web portals of Ecuavisa (Tv) and Super K800 (radio) when uploading some sports news on their digital platforms……….